Polymorphisms within autophagy-related genes influence the risk of developing colorectal cancer: a meta-analysis of four large cohorts - Sainz, Juan; García-Verdejo, Francisco José; Martínez-Bueno, Manuel; Kumar, Abhishek; Sánchez-Maldonado, José Manuel; Díez-Villanueva, Anna; Vodičková, Ludmila; Vymetálková, Veronika; Martin Sánchez, Vicente; Silva Filho, Miguel Inacio da; Sampaio-Marques, Belém; Brezina, Stefanie; et al. (Cancers, 2021)
The role of genetic variation in autophagy-related genes in modulating autophagy and cancer is poorly understood. Here, we comprehensively investigated the association of autophagy-related variants with colorectal cancer (CRC) risk and provide new insights about the molecular mechanisms underlying the associations. After meta-analysis of the genome-wide association study (GWAS) data from four independent European cohorts (8006 CRC cases and 7070 controls), two loci, DAPK2 (p = 2.19 × 10−5) and ATG5 (p = 6.28 × 10−4) were associated with the risk of CRC. Mechanistically, the DAPK2rs11631973G allele was associated with IL1 β levels after the stimulation of peripheral blood mononuclear cells (PBMCs) with Staphylococcus aureus (p = 0.002), CD24 + CD38 + CD27 + IgM + B cell levels in blood (p = 0.0038) and serum levels of en-RAGE (p = 0.0068). ATG5rs546456T allele was associated with TNF α and IL1 β levels after the stimulation of PBMCs with LPS (p = 0.0088 and p = 0.0076, respectively), CD14+CD16− cell levels in blood (p = 0.0068) and serum levels of CCL19 and cortisol (p = 0.0052 and p = 0.0074, respectively). Interestingly, no association with autophagy flux was observed. These results suggested an effect of the DAPK2 and ATG5 loci in the pathogenesis of CRC, likely through the modulation of host immune responses.
Gesehen am 12.05.2021